Tomographic imaging of the photonic environment of plasmonic nanoparticles - Anton Hörl (Nature Portfolio, 2017)
Imaging the photonic local density of states of plasmonic nanoparticles remains extremely challenging. Here, the authors introduce a tomography scheme based on electron microscopy that allows retrieval of the three-dimensional local density of states with nanometre spatial and sub-eV energy resolution.